Subject to Instability - Karen Bouwer (Studies in 20th & 21st Century Literature, 2000)
For Plantier, language constitutes reality and is male dominated. Readers of texts, she says, are at a disadvantage because the author imposes a logic that we must accept in order to understand the text. The discourses shaping our social reality have the same effect. Plantier has struggled against individual voices, discourses, and the very fabric of language informed by these discourses. "Subject to Instability" examines the impact on her generic evolution of a changing sense of self, of who her interlocutors are, and of those for whom she is speaking. I argue that her increasing attempt to juggle many different voices destabilizes her "monologic," poetical voice, resulting in a blurring of generic boundaries and eventually the abandonment of poetry. Recognizing that our entry into language is a form of alienation also unsettles Plantier because it undermines the very identity that allows her to speak for others. She concludes that each woman needs to become a Subject in her own right, but she continues to struggle against dominant discourses, modeling "resisting reader" strategies. If she can no longer practice "monologic steadfastness," this does not deter her from attempting to dismantle patriarchal language and striving to make her voice prevail over others.
Keywords: Plantier; language; reality; social reality; self; interlocutors; dominant discourses; male dominated discourses; women; patriarchal language